Farmer-led Innovations in Rice Farming System in the Flood-prone Ecosystem of Bangladesh - Alam, M Shahe; Husain, MM; Abedin, MZ (The Agriculturists, 2010)
Farmers in the flood-prone areas of Faridpur district have innovated rice-based farming technologies to improve their farm production and household income. One of such innovations is relay cropping of modern variety (MV) rice with jute. In order to investigate the detail socioeconomic issues of this farmer-led innovation, a survey-based study was undertaken during 2003. The analysis revealed that, following Jute + rice relay cropping method, farmers could enrich their farm productivity and household income. Farmers innovation involves lesser production costs compared to the conventional method and obtained much higher gross margin. Moreover, the new method proved to be advantageous in several ways: (i) the innovation involves about 6% less labour in MV Aman cultivation; (ii) under this technology, MV Aman rice can escape water stress in October, i.e. needs no supplemental irrigation; (iii) farmers have the scope of bearing almost 20% less input cost; and (iv) farmers can avoid the botheration of Aman seed bed preparation. Partial budget analysis further showed that, farmers could receive higher profit of Tk.4021/ha through MV rice production as relay cropping with Jute compared to that of rice production as sequential cropping.